ANALISIS IMPLEMENTASI PELAYANAN PRIMA TERHADAP KEPUASAN MASYARAKAT PADA KANTOR KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Rachmansyah, Dini Arif (PREDIKSI, 2014)
ABSTRACTÂ Implementation Analysis Service Excellence Against Public Satisfaction In District Office Samboja Kutai regency.The purpose of this study was to determine whether there is influence of excellent service to the District Office Samboja Kutai regency to the satisfaction of the District Samboja Kutai regency. The analysis tool used is the Simple Linear Regression. Mengguunakan census sampling method, with a total sample of 42 community Samboja District Office Kutai regency. of data obtained through questionnaires.The results of simple regression analysis between variables ON excellent service Samboja Kutai District Office Kartanegara.terhadap community satisfaction District Office Samboja Kutai regency equation Y = 9.9310964 + 0.7122 X. Further correlation r value of 0.708. After the results of the analysis are compared with the r table (table critical value) where N = 42 with a significance level of 0.05, it turns out empirical count r is greater than r table (0.708> 0.304> 0.393). Thus the working hypothesis (hi) be accepted as true and reject the null hypothesis (ho). This means that there is influence between the excellent service at the District Office Samboja Kutai District Kartaegara with community satisfaction Samboja Kartaegara Kutai regency.